2014
DOI: 10.1002/dvdy.24217
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting roles for MyoD in organizing myogenic promoter structures during embryonic skeletal muscle development

Abstract: Background Among the complexities of skeletal muscle differentiation is a temporal distinction in the onset of expression of different lineage-specific genes. The lineage-determining factor MyoD is bound to myogenic genes at the onset of differentiation whether gene activation is immediate or delayed. How temporal regulation of differentiation-specific genes is established remains unclear. Results Using embryonic tissue, we addressed the molecular differences in the organization of the myogenin and muscle cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…MyoD temporally orchestrates expression of multiple subsets of genes during the specification and differentiation stages of myogenesis [19]. Additionally, MyoD has been found to bind at sites throughout the genome where it induces histone modifications rather than gene expression [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MyoD temporally orchestrates expression of multiple subsets of genes during the specification and differentiation stages of myogenesis [19]. Additionally, MyoD has been found to bind at sites throughout the genome where it induces histone modifications rather than gene expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for MyoD, DNA binding affinity does not always correlate with transcriptional activation and instead, the timing and location of cofactor association may be the critical determinant for temporal and spatial activity. For example, genome-wide analysis has shown that MyoD transcriptional activity is temporally regulated through a direct repression of promoter-bound MyoD [19]. A comparison of the genome-wide promoter occupancy of both WT and phospho-mutant MyoD may reveal clues as to potential differential phospho-regulation of distinct downstream MyoD targets.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while genetic knockout studies confirm a role for Prmt5 in post-natal differentiation, they also show that Prmt5 is not required for embryonic skeletal muscle differentiation (85). However, molecular evidence demonstrates both Prmt5 and dimethylated H3R8 on the myogenin promoter in isolated somites dissected from E8.25-E9.5 embryos (86), suggesting that Prmt5 and H3R8 dimethylation are likely contributing to embryonic gene activation even if not absolutely required.…”
Section: The Chromatin State At Active Myogenic Locimentioning
confidence: 99%
“…This is facilitated, at least in part, by the continued association of MyoD with HDAC proteins at promoters that are not expressed until later in differentiation, even though other differentiation-specific genes are no longer bound by HDACs and co-repressors and are being actively transcribed (86, 91, 92). The functionality of this interaction was revealed by experiments demonstrating that ectopic expression of myogenin and Mef2D prevented HDAC association with promoters expressed at later times and resulted in premature expression of these genes (91).…”
Section: The Chromatin State At Active Myogenic Locimentioning
confidence: 99%
See 1 more Smart Citation